Analisis Model X-Score Zmijewski dalam Memprediksi Financial Distress Pada Industri Barang Konsumsi yang Terdaftar Di Bursa Efek Indonesia - Husni, Erdasti (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2017)
This Study aimed to test the X-Score Model Analysis Zmijewski In Predicting Financial Distress In Manufacturing Company Sector Consumer Goods Industry Listed on the Indonesia Stock Exchange. The population in this study are a Manufacturing Sector Consumer Goods Industry listed in Indonesia Stock Exchange during the period 2011 to 2015 as many as 37 companies. The sample is determined by purposive sampling with criteria for companies listed on the Indonesia Stock Exchange and companies that publish the complete annual financial statements the period 2011 to 2015 as many as 17 companies. Data used is secondary data obtained from www.idx.co.id. The analysis technique used was analysis using bankruptcy prediction model that is Zmijewski X-Score. So its results if its value (<0) or is negative then the company is in good financial condition or no bankruptcy, the Z-smallest value of -4.1519, and the value of Z-Top of -1.2751 and value Average -rata of -2.4763.